Prolonged grief, social contact, community belongingness: A representative study of loneliness among bereaved UK adults - James Cunningham; Eoin McElroy; Mark Shevlin (Acta Psychologica)
Background: Loneliness is a common experience among bereaved individuals, yet the extent to which prolonged grief, personal social contact, and community belongingness independently explain loneliness is not fully understood. Methods: We analyzed cross-sectional data from a nationwide, representative sample of 2520 adults in the UK who had lost a loved one. Hierarchical regressions were conducted in three steps, adding demographic and loss-related variables first, followed by personal contact and community belongingness, and then prolonged grief severity with loneliness as the outcome variable. Results: Bivariate correlations showed loneliness was significantly negatively associated with personal contact and community belongingness and positively associated with Prolonged Grief Disorder severity. In the final model, younger age, female gender, and lower income significantly predicted higher loneliness. Notably, community belongingness emerged as the strongest protective factor (β = −0.262), significantly outweighing the effect of personal social contact (β = −0.054). Higher prolonged grief also uniquely contributed to loneliness, with a non-linear relationship indicating a tipping point at severe grief levels that markedly exacerbated social isolation. Altogether, the final model explained approximately 24 % of the variance in loneliness. Conclusion: These findings underscore that individuals who exhibit intense prolonged grief and possess weaker connections to their broader community are especially vulnerable to loneliness. While more frequent personal contact can provide emotional intimacy, fostering a sense of community appears to confer broader, more sustainable social benefits. Interventions that integrate psychological support for severe grief and opportunities for community engagement may be particularly effective in reducing bereavement-related loneliness.